COVID-19 and neurological disorders: what might connect Parkinson’s disease to SARS-CoV-2 infection - Iacono, Salvatore; Schirò, Giuseppe; Davì, Chiara; Mastrilli, Sergio; Abbott, Michelle; Guajana, Fabrizio; Arnao, Valentina; Aridon, Paolo; Ragonese, Paolo; Gagliardo, Cesare; Colomba, Claudia; Scichilone, Nicola; et al. (Frontiers in Neurology, 2023)
SARS-CoV-2 infection leading to Coronavirus disease 19 (COVID-19) rapidly became a worldwide health emergency due to its elevated infecting capacity, morbidity, and mortality. Parkinson’s disease (PD) is the second most common neurodegenerative disorder and, nowadays the relationship between SARS-CoV-2 outbreak and PD reached a great interest. Apparently independent one from the other, both diseases share some pathogenetic and clinical features. The relationship between SARS-CoV-2 infection and PD is complex and it depends on the direction of the association that is which of the two diseases comes first. Some evidence suggests that SARS-CoV-2 infection might be a possible risk factor for PD wherein the exposure to SARS-CoV-2 increase the risk for PD. This perspective comes out from the increasing cases of parkinsonism following COVID-19 and also from the anatomical structures affected in both COVID-19 and early PD such as olfactory bulb and gastrointestinal tract resulting in the same symptoms such as hyposmia and constipation. Furthermore, there are many reported cases of patients who developed hypokinetic extrapyramidal syndrome following SARS-CoV-2 infection although these would resemble a post-encephalitic conditions and there are to date relevant data to support the hypothesis that SARS-CoV-2 infection is a risk factor for the development of PD. Future large, longitudinal and population-based studies are needed to better assess whether the risk of developing PD after COVID-19 exists given the short time span from the starting of pandemic. Indeed, this brief time-window does not allow the precise estimation of the incidence and prevalence of PD after pandemic when compared with pre-pandemic era. If the association between SARS-CoV-2 infection and PD pathogenesis is actually putative, on the other hand, vulnerable PD patients may have a greater risk to develop COVID-19 being also more prone to develop a more aggressive disease course. Furthermore, PD patients with PD showed a worsening of motor and non-motor symptoms during COVID-19 outbreak due to both infection and social restriction. As well, the worries related to the risk of being infected should not be neglected. Here we summarize the current knowledge emerging about the epidemiological, pathogenetic and clinical relationship between SARS-CoV-2 infection and PD.